TINGKAT PENGETAHUAN MAHASISWA JPOK UNIVERSITAS JAMBI TERHADAP OLAHRAGA PICKLEBALL - Alisia A.D Putri; Tri Bayu Norito; Bangkit Yudho Prabowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of knowledge of JPOK students at the University of Jambi regarding the sport of pickleball. The research employed a quantitative descriptive approach using a closed questionnaire consisting of 30 statement items as the research instrument. The population in this study consisted of 250 JPOK students from the 2025 cohort at the University of Jambi, with a sample of 50 students selected using a simple random sampling technique. The collected data were analyzed using descriptive percentage analysis with the assistance of SPSS software. The results of the study indicate that the overall level of knowledge of JPOK students at the University of Jambi regarding pickleball is in the moderate category. This is shown by a mean score of 52.07, with a minimum score of 30 and a maximum score of 73. The distribution of knowledge levels shows that 0% (0 students) are in the very low category, 12% (6 students) are in the low category, 76% (38 students) are in the moderate category, 12% (6 students) are in the high category, and 0% (0 students) are in the very high category. Based on these findings, it can be concluded that the level of knowledge of JPOK students from the 2025 cohort at the University of Jambi regarding pickleball is categorized as moderate, with a mean score of 52.07. These results indicate that students’ understanding of the basic concepts, techniques, rules, applications, analysis, and evaluation of pickleball games still needs to be improved through learning activities, socialization programs, and hands-on practice within the university environment.